Impact of Intrinsic and Extrinsic Motivation on Second Language Learning - Ullah, Shahid; Asif, Muhammad; Ajmal, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at establishing a relationship between motivation and second language learning. The students of intermediate level learning English as second language in public sector colleges of district Rajanpur constitute the population of this study. Two basic components of motivation namely Intrinsic motivation and extrinsic motivation have been measured with the help of Likert scale questionnaire Attitude Motivation Test Battery (AMTB).The researcher selected 50 items from this battery most relevant to the present study. Among them35 items belong to intrinsic motivation while rest of 15 are related to extrinsic motivation. English language learning achievement is measured through scores of the students they got n English in SSC examination. Data so collected was analyzed with the help of SPSS files (version 20) using T-test and ANOVA. It was found that students of district Rajanpur have a high level of motivation for learning English as second language. Study also showed that extrinsic motivation is greater as compared to intrinsic motivation. Moreover, girls showed higher level of motivation as compared to their male counterparts. Data analysis establishes a positive significant relationship between motivation and second language achievement.